(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research examines workplace harassment of women in India due to gender inequality. Few people believe that the Sexual Harassment of Women at Workplace (Prevention, Prohibition and Redress) Act, 2013, has had such a positive impact on working women and the workplace, particularly in the sector, in terms of establishing a method or remedy for penalising these types of offences. This essay’s goals are to educate readers on sexual harassment of women in India and identify the key causes of this problem in the workplace. To analyse the effectiveness of India’s Sexual Harassment of Women at Workplace (Prevention, Prohibition and Redressal) Act, 2013, in preventing sexual harassment in the workplace. The Vishaka norms served as the foundation for this demonstration. This study was conducted using certain doctrines.